Variabilities in symbiotic nitrogen fixation and carbon isotope discrimination among peanut (Arachis hypogaea L.) genotypes under drought stress. (29th July 2022) - Wang, Xu; Chen, Charles Y.; Dang, Phat; Carter, Joshua; Zhao, Shuli; Lamb, Marshall C.; Chu, Ye; Holbrook, Corley; Ozias‐Akins, Peggy; Isleib, Thomas G.; Feng, Yucheng
Abstract: Drought stress is one of the major environmental factors limiting peanut ( Arachis hypogea L.) productivity. Peanut response to drought varies depending on genotypic characteristics, crop growth stages, and environmental conditions. The objective of this study was to evaluate the effects of drought stress and rehydration on symbiotic nitrogen fixation and carbon isotope discrimination in peanut genotypes with varying drought tolerance. Experiments were conducted for 2 years in rainout shelters under three irrigation regimes: irrigated control, middle‐season drought with rehydration, and late‐season drought with rehydration. Reduction in percentages of shoot N derived from the atmosphere (%Ndfa) occurred under both drought treatments in both years; a greater reduction occurred under middle‐season drought than under late‐season drought. Middle‐season drought negatively affected carbon isotope discrimination in both years, although there were no significant differences under late‐season drought. Variabilities in %Ndfa and carbon isotope discrimination were found among different genotypes. Under middle‐season drought, both %Ndfa and carbon isotope discrimination were higher in drought‐tolerant lines than drought‐susceptible lines. The most drought‐tolerant lines had the highest N‐fixing capacity under both drought treatments. Additionally, there was a positive correlation between %Ndfa and carbon isotope discrimination under both drought treatments. In most genotypes, %Ndfa remained unchanged after rehydration; only a few genotypes showed a slight increase in %Ndfa after rehydration following both drought treatments. Our data suggested that symbiotic nitrogen fixation in many peanut genotypes was negatively affected by drought and may not recover from the damage caused by drought upon rehydration.